2011
DOI: 10.1111/j.1365-2702.2010.03656.x
|View full text |Cite
|
Sign up to set email alerts
|

Spanish nurses’ attitudes towards research and perceived barriers and facilitators of research utilisation: a comparative survey of nurses with and without experience as principal investigators

Abstract: Understanding different organisational and experience perspectives is important to identify challenges and opportunities to ensure research utilisation in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 51 publications
5
27
2
4
Order By: Relevance
“…However, when scrutinizing details in our findings and comparing these with an earlier Swedish study [23] and a Spanish study [39] where the same instrument was used, the nurses in the current study were less positive. This is discouraging since the network was expected to influence not only the facilitators but also their colleagues in the wards to use research findings in order to ensure evidence-based nursing.…”
Section: Discussioncontrasting
confidence: 38%
“…However, when scrutinizing details in our findings and comparing these with an earlier Swedish study [23] and a Spanish study [39] where the same instrument was used, the nurses in the current study were less positive. This is discouraging since the network was expected to influence not only the facilitators but also their colleagues in the wards to use research findings in order to ensure evidence-based nursing.…”
Section: Discussioncontrasting
confidence: 38%
“…A study conducted in Spain found that the top three barriers were related to the individual characteristics of the nurses, particularly their beliefs about the value of research and confidence in their research skills [8]. Being incapable of evaluating research quality was rated the greatest barrier by MorenoCasbas et al [8].…”
Section: Individual Factorsmentioning
confidence: 99%
“…A study conducted in Spain found that the top three barriers were related to the individual characteristics of the nurses, particularly their beliefs about the value of research and confidence in their research skills [8]. Being incapable of evaluating research quality was rated the greatest barrier by MorenoCasbas et al [8]. Inadequate skills in critical appraisal, lack of skills in accessing research and evaluating its quality, lack of confidence to implement change, and unfamiliarity with the research language have also been reported as barriers in the literature [12,15].…”
Section: Individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dünyada ve ülkemizde hemşirelerin araştırmaya ilişkin tutum ve farkındalıklarını belirlemeye yönelik pek çok çalışma yapılmıştır 12,[17][18][19][20][21][22] . Ancak hemşire öğrencilerin bu konudaki davranış ve farkındalığına yönelik yapılan çalışmaların yetersiz olduğu bilinmektedir 13 .…”
Section: Discussionunclassified